2001
DOI: 10.1055/s-2001-11331
|View full text |Cite
|
Sign up to set email alerts
|

Isokinetic Strength and Anaerobic Power of Elite, Subelite and Amateur French Soccer Players

Abstract: Information about the influence of different practice levels on physical characteristics of a large number of soccer players is lacking. Therefore we assessed muscular strength and anaerobic power of elite, subelite and amateur soccer players to clarify what parameters distinguish the top players from the less successful. We tested 95 soccer players from the French first division (elite), second division (subelite), and amateurs and determined the isokinetic strength of the knee extensor and flexor muscles at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

28
309
8
72

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 434 publications
(417 citation statements)
references
References 13 publications
28
309
8
72
Order By: Relevance
“…When football players of varying divisions were compared isokinetically, elite players exhibited higher knee flexor torque compared to sub-elite and amateur football players. This was found to be the case at all isokinetic speeds except at 300 °/sec, suggesting that hamstring strength plays an important role in joint balance and stabilization [13]. Research demonstrated that the probability of sustaining a hamstring injury is high if the concentric H/Q ratio, tested isokinetically at 60 °/sec, is less than 0.8 [12].…”
mentioning
confidence: 84%
“…When football players of varying divisions were compared isokinetically, elite players exhibited higher knee flexor torque compared to sub-elite and amateur football players. This was found to be the case at all isokinetic speeds except at 300 °/sec, suggesting that hamstring strength plays an important role in joint balance and stabilization [13]. Research demonstrated that the probability of sustaining a hamstring injury is high if the concentric H/Q ratio, tested isokinetically at 60 °/sec, is less than 0.8 [12].…”
mentioning
confidence: 84%
“…10 Knee extension may also be important for jumping which is regularly used as a measure of anaerobic power in soccer players. 3 However, it is unclear whether knee extensor strength affects other soccer related skills such as COD performance with and without a ball.…”
Section: Introductionmentioning
confidence: 99%
“…Strength and anaerobic power, particularly of the lower limbs, likely affects the explosive efforts of jumping, kicking and sprinting, which it has been argued may be key determinants of successful soccer performance. 3 As such, it may be important to consider training of these characteristics. Sprinting and high intensity efforts only represent 10-15% of covered running distance; however, they can be the most critical and decisive movements affecting the outcome of a game.…”
Section: Introductionmentioning
confidence: 99%
“…However, the force generated by a quadriceps contraction is many times what even the modified technique would be able to withstand [3,4,9,12]. Consequently, patients will still need to be immobilized.…”
Section: How Do We Get There?mentioning
confidence: 99%